Digitalization Of Arabic Language Learning Through Social Media/ رقمنة تعليم اللغة العربية من خلال وسائل التواصل الاجتماعي - Muhlis, Wachida; Rahmayanti, Indah; Fitrah, Isti Jayang; Muhamad, Sahrul; Hattab, Muhammad (Ijaz Arabi Journal of Arabic Learning, 2024)
The digitalization of Arabic language learning through social media focuses on the use of media that can be used as an introduction to the teaching process. Digitalization of learning is also a quite flexible alternative because it can be done anytime and anywhere. This type of research uses qualitative research with descriptive methods. The method in this research is a descriptive method, namely the researcher will utilize qualitative data and then explain it descriptively. This research was conducted to explore the digitalization of Arabic language learning through social media. Thus, the data used is based on library research, by reviewing and tracing various library literature. Data is searched for through texts both in books and articles and collected then analyzed and reduced deductively to produce research results that are narrated descriptively. The stages of data collection are: collecting several literature related to the focus of the research, reviewing and separating the data that is needed and not, reducing the data obtained and finally carrying out a descriptive conclusion. Digitalization of Arabic language learning through social media is an innovation that is very useful in facilitating access and expanding the reach of Arabic language learning. In today's digital era, social media has become one of the most effective platforms for conveying information and sharing knowledge with other people. Digitalization of Arabic language learning has many effectiveness that can be maximized by teachers and anyone else. We can use various devices such as WhatsApp, Google Drive, Google Form, Zoom, Instagram, Tiktok, Telegram, Facebook, YouTube and so on. Some of the benefits of digitizing Arabic language learning through social media include: Facilitating access and reach of Arabic language learning for people who live in remote areas or are difficult to reach by formal learning institutions, providing flexible learning time, because learning can be done anytime and anywhere course, without having to be physically present in the classroom, reduces learning costs, because there is no need to pay for transportation costs or expensive tutoring fees, opens up opportunities to study together with people from different countries or cultures, thereby increasing the learning experience and also expanding social networks , increasing learning motivation, because the digitalization of Arabic language learning through social media can be tailored to individual interests and needs.